The Relation between Concerning Work Creation with Licensing Organization by Local Governments (Law Number 11 of 2020) - Elmy Indrya Sukmawati; Helvis Helvis (Journal of Multidisciplinary Academic, 2021)
The condition of hyper regulation in Indonesia causes a lot of overlapping norms regulated in various laws and regulations. To overcome these problems, the idea to emerged this issue become several omnibus laws, including the Draft Law on Job Creation, which was promulgated as Law Number 11 of 2020 concerning Job Creation on November 2, 2020. Drafting of Law Number 11 of 2020 2020 concerning Job Creation with the omnibus law method raises several problems, including whether the use of the Omnibus Law technique in Law Number 11 of 2020 concerning Job Creation is in accordance with the technique of establishing laws and regulations as stipulated in Law Number 12 of 2011 concerning the Establishment Laws and regulations? Can the central government withdraw the authority of local governments in administering permits in the regions through Law Number 11 of 2020 concerning Job Creation The purpose of this study is to determine whether or not the use of the Omnibus Law technique in Law Number 11 of 2020 concerning Job Creation. It is contrary to the technique of establishing legislation in Law Number 12 of 2011 concerning the Establishment of Legislation. It also to find out whether or not the central government withdraws the authority of local governments in administering licensing in the regions through Law Number 11 of 2020 concerning Job Creation. The research method used in this study is normative juridical research, using a statutory approach and a conceptual approach. The conclusion of this study is that the omnibus law technique in the preparation of Law Number 11 of 2020 concerning Job Creation is contrary to the technique of drafting laws and regulations in Law Number 12 of 2011 concerning the Establishment of Legislation. Thus, in the future it is necessary to change the Act. -The law is to accommodate the method of law formation with the omnibus law method as a reference in the preparation of the draft law using the next omnibus method. The central government can withdraw the authority of local governments in administering permits that are sourced from the attribution authority in several laws, by making changes to the relevant laws that provide such authority.